KOMPOSISI HASIL TANGKAPAN DAN PENANGANAN HASIL TANGKAPAN UTAMA TRAWL PERMUKAAN DI DESA SEI BEROMBANG, KABUPATEN LABUHAN BATU, PROVINSI SUMATERA UTARA - Tyas Dita Pramesthy; Ratu Sari Mardiah; Rizky Wahyuda (Pusat Kajian Sumberdaya Pesisir dan Lautan IPB, 2020)
Most of the people on Sei Brombang Village work as fishermen. The dominant fishing gears used by fishermen in Sei Brombang village are surface trawl. The main catch is anchovy which is usually carried out directly by the handling process on the vessel by the fishermen. This study aims to determine the catch composition of surface trawl and to determine the handling techniques of the main catch from surface trawl. The main catch of surface trawling is anchovy (Stolephorus sp.) 75% of the total catch. Bycatch of surface trawl are 11% squid (Loligo sp.), 8% snapper (Lutjanus sp.), and 6% Parang-Parang fish (Chirocentrus sp.). Handling techniques of the main catch (anchovy) in a vessel with the stages: collecting the catch, sorting, washing, boiling, draining, and drying.